MULTIDIMENSIONAL STATISTICAL CLASSIFICATION BASED ON COMPOSITIONAL MODEL OF DATA DISTRIBUTION IN CASE UNDERFLOODING MONITORING - ZHUKOV, M.; TISHAIEVA, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This article is considered with outcome of experiments of remote sensing data interpretation. It is suggested new "compositional model" for describing statistical distribution data. This method was trained for estimation its efficiency. Results show reliable level of interpretation data. Therefore this approach has perspective to use in underflooding monitoring.